Traumatic right hemi-diaphragmatic injury: delayed diagnosis - Hassan Tavakoli; Jalal Rezaei; Seyed Amir Miratashi Yazdi; Mehdi Abbasi (Surgical Case Reports, 2019)
Abstract Background Traumatic diaphragmatic injury is known to present with the spectrum of symptoms, and most patients would have some symptoms due to abdominal organ herniation. Majority of injuries tend to present on the left hemidiaphragm but right-sided injuries also occur mostly with subtle, delayed presentation due to the buffering effect of the liver. Case presentation A 65-year-old male presented to the emergency department with a complaint of nausea and vomiting and reported no bowel movement or passing of flatus for 5 days. Upon further questioning, he recalled that he fell from a tractor while working in his farm 2 months earlier and sustained blunt trauma to his abdomen. Both chest and abdominal X-rays revealed the niveau formation of the small intestine on the right side above the liver and right hemidiaphragm. Further evaluation with CT scan confirmed the presence of a few small intestinal loops behind the liver and also in the chest through a rupture in the right hemidiaphragm. Exploratory laparotomy was performed. Some small intestine loops had gone behind the liver and through 4 cm rupture in the posterior aspect of the diaphragm into the chest. Displaced intestinal loops were relocated and no sign of ischemia or necrosis was observed. The patient was symptom-free within 2 days and he was discharged after 4 days. Conclusion Traumatic injuries of the diaphragm are rare, yet underestimated; therefore, they need a high index of suspicion for timely diagnosis and neglected diagnosis may present with a range of symptoms such as herniation months to years later.